The Sunday Assembly in Scotland: Vestiges of Religious Memory and Practise in a Secular Congregation - Cross, Katie (Practical theology, 2017)
This article draws on research undertaken with members of the Sunday Assembly, a secular congregation founded in London in 2013, which now has a presence in 70 cities worldwide. The Assembly has emerged into a space created by the current trend of secularism, and aims to provide its members to with the experience of a church-like congregation, without any religious or doctrinal elements. Yet interviews with members of the Assembly's congregation in Edinburgh expose a continuation of Christian practises, and a desire for further church-like elements, such as pastoral care. While secularism continues to occur in Scotland, this research would suggest that the process is not happening in a neat or linear fashion, and that those who identify as non-religious continue to have cause to draw on aspects of Christian memory and practise.